2016
DOI: 10.2460/javma.248.7.802
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocutaneous syndrome in Shih Tzus: 31 cases (1996–2014)

Abstract: Results suggested that HCS may have a heritable component in Shih Tzus, although the condition may also be identified in Shih Tzus without affected relatives. Clinical, clinicopathologic, ultrasonographic, and histologic abnormalities in affected Shih Tzus were similar to those previously reported for dogs of other breeds with HCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 31 publications
3
23
0
2
Order By: Relevance
“…In the present report, portosystemic shunting was ruled out based on CT angiography and on a second bile acids stimulation test, but iron or pyridoxine deficiencies were not investigated. Serum chemistry abnormalities were also consistent with previous HCS studies where ALKP has been reported to be consistently elevated and there is seldom elevation of total bilirubin 3 4 9. It is speculated that the cause of elevated ALKP is from induction due to skin lesions with acute phase inflammatory response or due to chronic illness-related glucocorticoid isoforms 4…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present report, portosystemic shunting was ruled out based on CT angiography and on a second bile acids stimulation test, but iron or pyridoxine deficiencies were not investigated. Serum chemistry abnormalities were also consistent with previous HCS studies where ALKP has been reported to be consistently elevated and there is seldom elevation of total bilirubin 3 4 9. It is speculated that the cause of elevated ALKP is from induction due to skin lesions with acute phase inflammatory response or due to chronic illness-related glucocorticoid isoforms 4…”
Section: Discussionsupporting
confidence: 89%
“…The severity of skin lesions appears to be a negative prognostic indicator in reported cases. Longest survival times have been recorded for dogs without cutaneous lesions or with less aggressive clinical signs 4. The skin lesions were milder at the time of presentation in this case study, which supports the slow or non-progressive nature of the disease.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In contrast to people, the majority of dogs with SND have nonglucagonomarelated disease associated with an underlying hepatopathy typically of unknown etiology or associated with phenobarbital administration. Diseases that have been reported to occur concurrently with SND in dogs includes diabetes mellitus and hyperadrenocorticism (1,2,(5)(6)(7)(8)(9)(10)(11). The specific pathomechanism of the hepatic form of SND in dogs is unknown but is postulated to occur secondary to metabolic disturbances that result in increased hepatic catabolism of amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Medical management in dogs with SND because of nonglucagonoma-related disease, similar to people with pseudoglucagonoma syndrome, is aimed at treating the underlying condition and repletion of various nutrients including zinc, essential fatty acids, and amino acids (1,4,11). Parenteral administration of amino acids is preferred in both people and dogs with SND over the oral route in order to bypass portal circulation and an exaggerated hepatic first pass effect (1,2,4).…”
Section: Discussionmentioning
confidence: 99%